2012
DOI: 10.1159/000337016
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and Rehabilitation of Visual Field Defects in Stroke Patients: A Retrospective Audit

Abstract: Objective: Visual field defects (VFD) after stroke can cause significant disability and reduction in quality of life. Adequate diagnosis of VFD and referral to visual rehabilitation are important to improve outcome. Our aim was to conduct a retrospective clinical audit to investigate how neurologists detect and follow up VFD in stroke patients in a university hospital in Norway. Methods: All patients registered in the Bergen NORSTROKE Registry from February 2006 to May 2009 with (1) occipital lobe infarctions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Medical examination at the time of admission consisted of medical history and somatic and neurological status. The examination included test of visual function with the Snellen visual acuity test chart and test of the visual field with Donder's test . All patients underwent opthalmological examination with a perimeter either before referral or during their stay in the rehabilitation unit.…”
Section: Methodssupporting
confidence: 84%
“…Medical examination at the time of admission consisted of medical history and somatic and neurological status. The examination included test of visual function with the Snellen visual acuity test chart and test of the visual field with Donder's test . All patients underwent opthalmological examination with a perimeter either before referral or during their stay in the rehabilitation unit.…”
Section: Methodssupporting
confidence: 84%
“…Otherwise it is difficult to see a pattern in the referrals; at least it is difficult to connect patients' symptoms with a referral. Sand et al (29) showed in a Norwegian study only 9% of their patients with VFD were referred to perimetry, and 8% to vision rehabilitation. These results indicate a lack of connection between the eye specialists, neurorehabilitation and acute care units.…”
Section: Ophthalmologist Assessment (Q18)mentioning
confidence: 99%
“…Vision problems have also been shown to have a substantial effect on quality of life [10][11][12][13] and on activities of daily life (ADL) [1,2,14,15]. Still, stroke patients with vision problems are rarely offered thorough investigation and/or visual rehabilitation [16]. Lately, vision problems after stroke have received increasing attention.…”
Section: Introductionmentioning
confidence: 99%